Aging and blood pressure. - Mendes, Romeu (2008)
High blood pressure is a major risk factor of cardiovascular diseases and has a high prevalence in the older individuals becoming in a risk factor associated with high cardiovascular mortality and morbidity among these population. This study has the objective to analyze the changes in the cardiovascular system inherent to the aging process, that provoke the increase of blood pressure levels with the advance of age and that can origin hypertension. With the aging process, changes in the anatomy and cardiovascular physiology occur, even in the absence of illness. High blood pressure is characterized as a systemic condition that involves the presence of structural changes of the arteries and the myocardium, associated to an endotelial and baroreceptors dysfunction.